Interrelations: Blake and Yeats - Billigheimer, Rachel V. (ABEI Journal, 2003)
Both Blake and Yeats were prophets of their own time and annunciators of the future. Both used a rich mythological structure of symbols to communicate the universality and unity of their ideas. The Illuminated Books present a prophetic view, one which projects the future. Yeats’ search into the Spiritus Mundi, the origin of all images, may be seen in terms of Blake’s archetypal forms. Dance, symbolizing destructive human passions which prohibit the individual’s entry into the luminous circle of perfection, can be found employed analogously in the work of both poets. Whereas Blake had always decried the sadistic Female Will or Sphinx, Yeats is influenced by the Nietzschean acceptance of joy in pain and this is the triumph of A Full Moon in March. In Yeats the dance signifies the height of passionate abandonment. Yeats’ apocalyptic dancers or goddesses are basically Blake’s archetypal roles of the Female. The Female in Blake represents paradoxically the elements of both complete unity and conflict in the male. Both Blake and Yeats see the feminine principle as controlling human destiny. These archetypal images are related through their role of prophecy. Both Blake and Yeats denigrate reason, law, science and materialism. However, while Blake deplores the possessive Female Will in its obstruction of the imagination through the force of materialism, the binding to nature, bringing destruction to humanity, Yeats’ heroes are created from suffering and destruction. While Blake urges the fulfilment of the imaginative or eternal life through the liberated life of the senses and denounces the exclusively material world as frigid and dark, Yeats, in his final vision, urges the fulfilment of sensual experience, acclaiming heroic suffering through tragedy as creative joy, which transcends the world of time.